SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL ACTIVITY OF SOME SCHIFF BASE METAL COMPLEXES - Mohammed, Samar S. (Journal of Medical Genetics and Clinical Biology, 2024)
This study presents the synthesis and characterization of five metal complexes (C1–C5) derived from the reaction of a newly synthesized ligand (HL) with various metal chlorides, specifically Zn, Co, Ni, Mn, and Fe. General Background: Transition metal complexes have garnered significant interest due to their diverse biological activities and potential therapeutic applications. Specific Background: The ligand (HL) was synthesized from equimolar amounts of p-anisidine and salicylaldehyde, yet the influence of different metal ions on the biological properties of such complexes remains underexplored. Knowledge Gap: While several metal complexes exhibit antimicrobial properties, there is limited research on the biological activities of complexes formed with this specific ligand. Aims: This work aims to synthesize and characterize the metal complexes and evaluate their antibacterial activity against various bacterial strains. Results: Characterization via FT-IR and ¹H NMR spectroscopy confirmed the successful formation of the complexes, indicating strong metal-ligand interactions. Preliminary biological testing revealed varying degrees of antibacterial activity among the complexes, with notable effectiveness against certain bacterial strains. Novelty: The study contributes to the understanding of how different metal ions influence the biological properties of metal-ligand complexes. Implications: These findings suggest that the synthesized metal complexes could serve as potential candidates for further development in antimicrobial therapies, prompting additional research into their mechanism of action and broader biological applications.